2011
DOI: 10.1016/j.ajog.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Higher infant body fat with excessive gestational weight gain in overweight women

Abstract: Objective Gestational weight gain (GWG) is positively associated with birth weight and maternal pre-pregnancy BMI is directly related to infant fat mass (FM). This study examined whether differences exist in infant body composition based on 2009 GWG recommendations. Study Design Body composition was measured in 306 infants and GWG was categorized as appropriate or excessive. Analysis of covariance was used to investigate the effects of GWG and pre-pregnancy BMI and their interaction on infant body compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 26 publications
8
136
2
1
Order By: Relevance
“…Recent findings demonstrate that neonates born from overweight mothers who exceed GWG recommendations have greater body fat percentage and greater fat mass compared to their offspring born to women who gained within the guidelines [60] which strengthens previous findings suggesting a strong link between GWG and downstream childhood obesity [61,62].…”
Section: Maternal Obesity Gestational Weight Gain Insulin Resistancsupporting
confidence: 74%
“…Recent findings demonstrate that neonates born from overweight mothers who exceed GWG recommendations have greater body fat percentage and greater fat mass compared to their offspring born to women who gained within the guidelines [60] which strengthens previous findings suggesting a strong link between GWG and downstream childhood obesity [61,62].…”
Section: Maternal Obesity Gestational Weight Gain Insulin Resistancsupporting
confidence: 74%
“…Among the 20 articles that met the inclusion criteria, six included both exposures 6,27,28,29,30,31 . The average score of the selected articles was 15.4, with a minimum of 13 and a maximum of 18.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the prevalence of maternal obesity in recent decades 9,10 has occurred in parallel with the increment of large for gestational age newborns 11,12,13 and an increased incidence of childhood obesity 14 . Female offspring of obese women are most likely to be obese predisposing their children to obesity, insulin resistance and diabetes 6,15,16 . Several studies have shown that a high increment in maternal gestational weight gain associated with increased offspring body mass index (BMI) 17,18,19 whereas other studies have reported no such association 20,21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of excessive GWG have been increasing over me and research has shown that greater GWG is associated with increased weight of baby at birth and infancy [24][25][26][27] . This raises ques ons about the long-term adverse eff ects of higher weight gains in pregnancy.…”
Section: Discussionmentioning
confidence: 99%